وصمة المرض النفسي و نتائجها السلبية على المريض النفسي - نبار, ربيحة (University of Eloued جامعة الوادي, 2018)
غالبا ما يرتبط المرض النفسي كالاكتئاب أو الفصام باعتقادات غير صحيحة و قد لا يرتبط بأمراض أخرى كارتفاع ضغط الدم أو السكري ، و ذلك لكون المرض النفسي ذو أصل عضوي و أسبابه خارجة عن إرادة المريض وليس كما يظن البعض بأنه سوء في الخلق أو ضعف في الروح ، فينظرون إلى المريض النفسي نظرة ازدراء و دونية مما يخلق وصمة عار على المريض تؤدي به إلى الصمت و الإنكار و عدم الاعتراف بمرضه و انفضاض أهله و ذويه من حوله و تمنعه من اللجوء إلى خدمات الصحة النفسية للحصول على العلاج ، بالإضافة إلى ما تسببه الوصمة من التمييز و عدم العدل و الإنصاف في مجالات عديدة و حرمانه من الكثير من المزايا . The stigma of psychological illness and its negative consequences on the patient Abstract : Psychological illness, such as depression or schizophrenia, is often associated with incorrect beliefs and may not be associated with other diseases such as high blood pressure or diabetes. This is because the mental illness is of organic origin and its causes are beyond the patient's will and not as some think it is bad in creation or weakness in spirit, They see the psychological patient as a contempt and inferiority, which creates a stain on the patient leading to silence and denial and non-recognition of his illness and the rejection of his family around him and prevent him from resorting to mental health services for treatment, In addition to the stigma of discrimination, unfairness and equity in many areas and depriving him of many advantages.
The stigma of psychological illness and its negative consequences on the patient
مجلة الدراسات والبحوث الاجتماعية المجلد 06 العدد 04 جامعة الوادي
Keywords: المريض النفسي، الوصمة، المرض النفسي; Psychiatric patient, stigma, psychological illness